Correlation between ground motion intensity measures and seismic damage of 3D R/C buildings. (1st January 2015) - Kostinakis, Konstantinos; Athanatopoulou, Asimina; Morfidis, Konstantinos
Highlights: We studied the correlation between seismic intensity measures (IMs) and damage level. NTHA were performed accounting for the orientation of seismic motion. The damage parameters based on displacement demands do not correlate well with OSDI. Sa ( T 1 ) and velocity related IMs show the largest correlation with interstorey drift. The OSDI shows medium or poor correlation with the majority of the IMs. Abstract: The present paper investigates the correlation between a large number of widely used ground motion intensity measures (IMs) and the corresponding damage to medium-rise 3D, R/C buildings. To accomplish this purpose the seismic performance of two symmetric and two asymmetric in plan 5-storey buildings subjected to 64 bidirectional earthquake ground motions are determined. Structural performance is expressed in terms of the maximum and the average interstorey drift as well as the overall structural damage index and it is determined for many angles of seismic incidence. For each individual pair of accelerograms and each seismic input angle the values of the aforementioned seismic damage measures are determined. Then, the correlation between the damage measures and the IMs is evaluated. The results reveal that the spectral acceleration at the fundamental period of the structure shows the strongest correlation with the maximum and average interstorey drifts, followed by the velocity related seismic IMs. Moreover, the vast majority of the examined ground motion IMs are proved to be inadequate to predict the overall structural damage index of frame-wall (dual) systems.